More on possible Forest Enets – Ket contacts - Florian Siegl (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2012)
In this paper linguistic traces of the Enets’ migration to the Taimyr Peninsula are addressed. Special attention is paid to Forest Enets–Ket contacts and a tentative etymology for the (Forest) Enets’ ethnonym for Kets and Selkups is offered. Of special importance is a likely Enets place name in Northern Evenkija, an area from which no Enets place names have been reported earlier. As the same area is inhabited by speakers of the northern dialect of Ket, this area should be seen as a possible contact area for the unusual case of pronoun borrowing in Forest Enets as discussed in Siegl (2008)